Analysis of Factors Causing Low-Cost Carrier Airlines' Customer Satisfaction at Soekarno Hatta Airport - Koharudin, Muhammad; Simarmata, Juliater (Dinasti International Journal of Digital Business Management, 2024)
The scientific literature review article entitled Analysis of Factors Causing Customer Satisfaction of Low-cost Carrier Airlines at Soekarno Hatta Airport is in the domain of marketing management science. The purpose of this article is to formulate a hypothesis regarding the interrelationship of various aspects, which will then be used as a basis for further research in the field of human resource management. This research uses a qualitative descriptive research methodology. The data used in this research comes from previous research which is still relevant to this research. Information is collected from leading scientific online platforms, such as Publish or Perish, Google Scholar, digital reference books, and the journal Sprott. The results obtained from this research are presented as follows: 1) Punctuality of flight times influences customer satisfaction of low-cost carrier airlines at Soekarno Hatta Airport; 2) The service quality of low-cost carrier airlines influences customer satisfaction of low-cost carrier airlines at Soekarno Hatta Airport; and 3) Aviation safety standards influence customer satisfaction of low-cost carrier airlines at Soekarno Hatta Airport.